Predictors of good glycemic controls among type 2 diabetes mellitus patients in two primary health clinics, Kuala Selangor - Abdullah, Nurul Ain; Ismail, Suriani; Shariff Ghazali, Sazlina; Juni, Muhamad Hanafiah; Kadir @ Shahar, Hayati; Aziz, Noor Rafizah Aminah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The objective of this study was to determine the factors and predictors of good glycaemic control among patients with Type 2 Diabetes Mellitus (T2DM) in two rural government health clinics in Kuala Selangor. Methods: This cross-sectional study involved 200 patients selected through systematic random sampling from a list of T2DM patients in two government health clinics in Kuala Selangor. Data was collected using a self-administered questionnaire while glycosylated haemoglobin (HbA1c) results were obtained from the patients’ blood results record at the clinic. HbA1c of 6.5 % and below was categorized as good glycaemic control. The factors studied were socio-demographic characteristics (age, gender, ethnicity, level of education, occupation and household income), T2DM medical history (T2DM duration and type of treatment), diabetes knowledge, health literacy, adherence to treatment, body mass index (BMI) and physical activity. Pearson’s chi square test was used to test for associations and multiple logistic regressions were used to determine the predictors. Results: The response rate was 86.9%. The pro-portion of good glycaemic control was 34.0%. Level of glycaemic control was significantly associated with duration of being diagnosed with T2DM (p=0.006) and type of treatment (p=0.009). The probability of having good glycaemic control was 2.5 times more likely among respondents diagnosed with T2DM for less than 10 years (AOR=2.458, 95% of CI=1.504-14.282, p=0.037). Conclusion: Shorter duration of being diagnosed with T2DM has been found to be a predictor of good glycaemic control in this study population, thus warranting stricter monitoring among patients who have been diagnosed for a longer period.